Online social networking usage and frequency of Depression in Undergraduate University students - Balouch, Muhammad Ali; Kausar, Rukhsana; Abbassi, Muhammad Ali; Soomro, Saifullah; Khan, Shahida; Ansari, Muhammad Ibrahim (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Mental health is playing an important role in our daily life. Now a days depression is the second most common illness in the world. Online social networking is one of the risk factors to mental illness, and objective is to determine the usage of social networking sites (SNS) and level of depression among undergraduate students. METHODOLOGY: This cross-sectional study was conducted at Sindh Agriculture University Tandojam- Sindh with simple random sampling through self-administrated questionnaires. Sample size was calculated on a prevalence rate of 50%, students ranging from 17-28 years, using SNS were included while those having any chronic illness were excluded. Ethical approval was obtained from Health Services Academy Islamabad, anonymity confidentiality, and privacy was assured. SPSS version 20.0 was used, and chi-square was applied to find the association. RESULTS: Out of 212 students, the respondents consisted mainly of male students n=165 (77.8%), among them, 52 (24.5%) students were of age 19 years and 76 (35.8%) were in first-year class. Results reveal that the frequently used SNS was Facebook 169 (79.7%). The students using these sites for more than 4 years were 28 (13.2%). Among the SNS users, 142(67%) were having moderate depression, while 9 (4.2%) had severe depression. Male students have more online friends (p <0.001) and tend to login more times on SNS as compared to female students (p=0.023). CONCLUSION: The usage of social networking sites is more among undergraduate university students, especially males. Most of the students suffered from moderate depression. There may be a link between SNS usage and depression among undergraduate university students.